EDUKASI KONSEP RUMAH HUNIAN SEDERHANA TAHAN GEMPA DI WILAYAH SEISMIK TINGGI - Meity Wulandari; Krisna Dwi Handayani; Alwan Gangsar Brilian Putra; Mochamad Firmansyah Sofianto; Erina Rahmadyanti; Mas Suryanto HS; Bambang Sabariman; Yogie Risdianto; Danayanti Azmi Dewi Nusantara; Muhammad Imaduddin (Jurnal Abdi Masyarakat, 2026)
Davao City, Philippines, is located in a high seismic zone along the Pacific Ring of Fire, where residential buildings are highly vulnerable to earthquake damage. This community service program aimed to improve earthquake risk awareness and understanding of simple earthquake-resistant housing concepts among students and teachers of Sekolah Indonesia Davao (SID). The program was conducted through preparatory coordination, educational implementation, and evaluation stages. Educational activities included pre-tests, distribution of booklets, lectures on basic structural principles of earthquake-resistant houses, video demonstrations, discussions, and post-tests. The results showed a significant improvement in participants’ understanding, with correct responses increasing from 36% in the pre-test to 82% in the post-test. Participant feedback also indicated high satisfaction with the relevance, clarity, and usefulness of the materials. The program demonstrates that school-based education can serve as an effective community-based earthquake mitigation strategy in high seismic regions.